Administrative and Legal Status of Canine Units of the National Police of Ukraine: Essence and Content - V. V. Garmash (Law and Safety)
The scientific article is focused on the coverage of scientific approaches to understanding such concepts as “legal status”, “administrative and legal status”, “administrative and legal status of canine units of the National Police of Ukraine”, resulting in the provision of characteristics of the administrative and legal status of canine units of the National Police of Ukraine.